Influence of soil nutrients on the presence and distribution of CPR bacteria in a long-term crop rotation experiment - Santana-Pereira, Alinne L. R.; Moen, Francesco S.; Severance, Beatrice; Liles, Mark R. (Frontiers in Microbiology, 2023)
Bacteria affiliated with the Candidate Phyla Radiation (CPR) are a hyper-diverse group of ultra-small bacteria with versatile yet sparse metabolisms. However, most insights into this group come from a surprisingly small number of environments, and recovery of CPR bacteria from soils has been hindered due to their extremely low abundance within complex microbial assemblages. In this study we enriched soil samples from 14 different soil fertility treatments for ultra-small (<0.45 m) bacteria in order to study rare soil CPR. 42 samples were sequenced, enabling the reconstruction of 27 quality CPR metagenome-assembled genomes (MAGs) further classified as Parcubacteria/Paceibacteria, Saccharibacteria/Saccharimonadia and ABY1, in addition to representative genomes from Gemmatimonadetes, Dependentiae and Chlamydae phyla. These genomes were fully annotated and used to reconstruct the CPR community across all 14 plots. Additionally, for five of these plots, the entire microbiota was reconstructed using 16S amplification, showing that specific soil CPR may form symbiotic relationships with a varied and circumstantial range of hosts. Cullars CPR had a prevalence of enzymes predicted to degrade plant-derived carbohydrates, which suggests they have a role in plant biomass degradation. Parcubacteria appear to be more apt at microfauna necromass degradation. Cullars Saccharibacteria and a Parcubacteria group were shown to carry a possible aerotolerance mechanism coupled with potential for aerobic respiration, which appear to be a unique adaptation to the oxic soil environment. Reconstruction of CPR communities across treatment plots showed that they were not impacted by changes in nutrient levels or microbiota composition, being only impacted by extreme conditions, causing some CPR to dominate the community. These findings corroborate the understanding that soil-dwelling CPR bacteria have a very broad symbiont range and have metabolic capabilities associated to soil environments which allows them to scavenge resources and form resilient communities. The contributions of these microbial dark matter species to soil ecology and plant interactions will be of significant interest in future studies.